Analisis Kinerja Keuangan NU Care-LAZISNU PBNU Periode 2016-2022 - Niam, Ahmad Mukafi (Accounting Department UNUSIA, 2024)
This research on the financial performance of the zakat management organization (OPZ) is a case study on NU Care-LAZISNU, the Central Board of Nahdlatul Ulama's (PBNU) zakat management institution under the Islamic organization Nahdlatul Ulama. The research method used is descriptive qualitative by conducting in-depth analysis of financial reports for the period 2016-2022. This period covers all years after the institution was recognized as a national LAZ. There are four variables analyzed, namely activity ratios, operational ratios, liquidity ratios, and growth ratios. Each ratio has several derivative ratios. The research results show that NU Care-LAZISNU PBNU has very good financial performance, which means it has the ability to manage ZIS funds with very high levels of effectiveness and efficiency, has very good liquidity, and is able to grow optimally. However, there are several derivative ratios that need to be improved, such as fund turnover ratio and operational efficiency ratio.